2017
DOI: 10.3382/ps/pew228
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and sensitive detection of Mycoplasma synoviae by an insulated isothermal polymerase chain reaction-based assay on a field-deployable device

Abstract: Mycoplasma synoviae (MS), causing respiratory diseases, arthritis, and eggshell apex abnormalities in avian species, is an important pathogen in the poultry industry. Implementation of a biosecurity plan is important in MS infection management. Working on a field-deployable POCKIT™ device, an insulated isothermal polymerase chain reaction (iiPCR) assay has a potential for timely MS detection on the farm. The MS iiPCR assay had limit of detection 95% of about 9 genome equivalents by testing serial dilutions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The iiPCR technology and a commercially available field-deployable device (POCKIT™ combo system), which includes a taco™ mini Automatic Nucleic Acid Extraction System and a POCKIT™ Nucleic Acid Analyzer (GeneReach USA, Lexington, MA, USA), allow automatic detection and interpretation of PCR results within 1-1.5 h [36]. It has been shown that iiPCR or RT-iiPCR assays have excellent sensitivity and specificity for the detection of various targets, including swine pathogens, such as classical swine fever virus (CSFV), FMDV, porcine epidemic diarrhea virus (PEDV), porcine deltacoronavirus (PDCoV), and porcine reproductive and respiratory syndrome virus (PRRSV) [38][39][40][41], and various pathogens in shrimp, dogs, cats, poultry, ruminants, and horses [42][43][44][45][46][47][48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…The iiPCR technology and a commercially available field-deployable device (POCKIT™ combo system), which includes a taco™ mini Automatic Nucleic Acid Extraction System and a POCKIT™ Nucleic Acid Analyzer (GeneReach USA, Lexington, MA, USA), allow automatic detection and interpretation of PCR results within 1-1.5 h [36]. It has been shown that iiPCR or RT-iiPCR assays have excellent sensitivity and specificity for the detection of various targets, including swine pathogens, such as classical swine fever virus (CSFV), FMDV, porcine epidemic diarrhea virus (PEDV), porcine deltacoronavirus (PDCoV), and porcine reproductive and respiratory syndrome virus (PRRSV) [38][39][40][41], and various pathogens in shrimp, dogs, cats, poultry, ruminants, and horses [42][43][44][45][46][47][48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…The equipment including an automated nucleic acid extraction system (taco TM mini) required for iiPCR (POCKIT TM Nucleic Acid Analyzer a , POCKIT TM ) is specifically designed with the option of using batteries as an electrical power source and lyophilised reagents avoiding the need for a cold chain to be fully field-deployable [26]. This enables it to be used for point of need diagnosis plus results are obtainable within 1 h. Moreover, a number of assays have been successfully developed for detection of pathogens associated with humans, companion animals, livestock and farmed aquatic species based on the iiPCR/POCKIT TM system and all have been shown to have equivalent specificity and sensitivity to RT-qPCR [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. In this report, an EIAV RT-iiPCR based on the POCKIT TM system designed to aid in the diagnosis of EIAV-infected equids was evaluated by comparison with a conventional EIAV RT-qPCR assay, where both assays targeted the same region of the viral genome although not using identical primers and probes.…”
Section: Introductionmentioning
confidence: 99%
“…The POCKIT iiPCR system provides an efficient and cost‐effective alternative for mass testing of high‐risk dogs for B. gibsoni . Although this study focused on B. gibsoni , the field‐deployable iiPCR platform has potential to aid in rapid detection of a variety of animal and human infections under field conditions …”
Section: Discussionmentioning
confidence: 99%